Evaluation of intraoperative microwave coagulo‐necrotic therapy (MCN) for hepatocellular carcinoma: a single center experience of 719 consecutive cases. Issue 3 (March 2013) - Takami, Yuko; Ryu, Tomoki; Wada, Yoshiyuki; Saitsu, Hideki
Abstract Background Hepatic resection (HRx) or radiofrequency ablation may be carried out as the first‐line treatment of hepatocellular carcinoma (HCC). However, we have used intraoperative microwave ablation, named microwave coagulo‐necrotic therapy (MCN) as part of our strategy for the treatment of HCCs for more than 15 years. Here we describe the treatment outcomes achieved at our institution as a high‐volume center for microwave ablation. Methods Between July 1994 and December 2010, 719 consecutive patients received MCN as their initial therapy for HCC (mean tumor size 26.9 mm, mean number of lesions 2.51) at our institute. The therapeutic survival effect, local tumor progression, and overall recurrence were prospectively evaluated and statistically analyzed. Results The 1‐, 3‐, 5‐, 7‐, and 10‐year overall survival rates of all 719 patients were 97.7, 79.8, 62.1, 45.3, and 34.1 %, respectively. Thirty percent of the patients had Child—Pugh class B cirrhosis and the 5‐year survival rate of these patients was 46.6 %. The 5‐year survival of patients with ≥4 lesions (n = 168) was 49.6 % and that of patients meeting the Milan criteria (n = 470) was 70.9 %. The 1‐, 3‐, 5‐, 7‐, and 10‐year overall survival rates for 390 patients treated with MCN who had ≥3 lesions with diameter ≥3 cm were 97.9, 85.1, 70.0, 57.1, and 43.0 %. No significant differences were found between the overall survival rates after MCN and the overall survival rates in 34 patients treated with HRx during the same period at our institute and under the same (P = 0.3592), nor were there any differences in disease‐free survival (P = 0.3496) and local recurrence rates between the MCN and HRx groups (P = 0.5926). Conclusion MCN is effective for the locoregional control of HCC, with results comparable to those of HRx. MCN should be considered as one of the first‐choice treatments for HCC, even for patients with poor liver function or multiple lesions.